Hubungan antara Persepsi Bystander dan Kelekatan Orang Tua dengan Cyberbullying pada Remaja - Alia, Ludfi Shofiatul; Malay, M Nursalim; Izzati, Indah Dwi Cahya (Universitas Muhammadiyah Metro, 2022)
Cyberbullying is aggression intentionally and repeatedly carried out in an electronic context, such as Instagram, Facebook, and other social media, against someone who cannot easily defend themself. This quantitative research was conducted on 148 adolescent students in a private school in Central Lampung. This study uses a scale of cyberbullying, bystander, and parental attachment. The result is a linear regression test using JASP 0.16.0. The analysis showed the coefficient of R2 was 0.714, which means that the perception of bystanders and parental attachment can affect cyberbullying by 71.4%. The results of the correlation coefficients of the three variables are equal to the meaning of this study, indicating that there is a relationship with a positive direction between the bystander variable and the parental attachment variable with the cyberbullying variable.